Relationship in Principle between Corporate Governance, Intellectual Capital Disclosure and Firm Performance - Mainoma, Hauwa’u Muhammad; Nasir, Aliyu Muhammad (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2023)
This conceptual paper's goal is to discuss the relationship between business performance, intellectual capital disclosure, and corporate governance. This work proposes hypotheses about the relationship between corporate governance, intellectual capital disclosure, and business performance with the use of signaling theory. Their relationship's structure should inform all stakeholders about how corporate governance affects business performance. This demonstrates how well the governance is performing its duties to increase intellectual capital disclosure, which calls for essential adjustments to corporate procedures. It reveals the connection between the board nominating committee, the disclosure of intellectual capital, and corporate performance.